A rare case of parental iron-induced persistent hypophosphatemia - Abigayle Sullivan; Theresa Lanham; Adam Rubin (Greater Baltimore Medical Center, 2020)
We report a case of an African American woman who presented with fatigue, generalized weakness, and hypophosphatemia in the setting of a recent hospitalization for severe, symptomatic iron deficiency anemia requiring ferric carboxymaltose infusions. Parental iron is indicated in numerous clinical settings including chronic kidney disease, inflammatory bowel disease, and iron deficiency anemia. Ferric carboxymaltose is one of the most common forms of parental iron infusions used due to administration procedure and minimal reported side effects. The most common side effect reported is a transient decrease in serum phosphate. This case highlights the necessity of monitoring serum phosphate in the setting of parental iron infusions, especially ferric carboxymaltose, and when severe hypophosphatemia occurs management includes intravenous phosphorous and calcitriol.